(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This study examines the geological processes shaping the Fergana Valley, an intermontane basin in Central Asia characterized by active tectonics, complex sedimentary dynamics, and significant geomorphological activity. Using a multidisciplinary approach involving field surveys, geophysical modeling, and remote sensing, the research highlights key phenomena, including fault displacement rates of 4.2–5.6 mm/year, sediment thickness exceeding 10 km, and erosion rates of 1.3–1.8 mm/year. The findings reveal critical seismic hazards, untapped hydrocarbon potential, and increasing geomorphological instability, offering actionable insights for sustainable development and regional collaboration. Predictive models emphasize ongoing tectonic uplift and resource challenges, underscoring the need for integrated risk management strategies.